Malignant intestinal obstruction during twin pregnancy: surgical resection of a myxoid liposarcoma without induction of labour. Issue 7 (8th July 2019) - Paasch, Christoph; Isbruch, Annette; Strik, Martin W; Siegel, Robert
Abstract : Myxoid liposarcoma (MLS) represents one of the three main morphological subgroups of liposarcomas. Extrapulmonary recurrence to the retroperitoneum and abdomen is common in MLS. A pregnant patient was referred to our hospital due to abdominal pain and obstipation. In the past, she had received a multimodal treatment of an MLS of the left dorsal thigh. Now, MRI revealed a 14.6×10.1×12.4 cm-sized tumour adjacent to the uterus with a known twin pregnancy (26th week). We performed surgery under tocolytic therapy. The tumour has been completely removed. The histopathological examination revealed a nodular manifestation of a moderately differentiated MLS arising from the mesentery. Eleven weeks later, our patient delivered healthy twins. This is the first report of surgical resection of MLS during a twin pregnancy. With a multidisciplinary approach and a concerted treatment by surgeons and obstetricians, surgical resection resolved malignant intestinal obstruction and enabled an uncomplicated continuation of pregnancy.